(untitled) (Student’s Journal of Health Research Africa, 2022)
Background: The growth in the poultry and fish industry in Uganda has resulted in heavy dependence on finished feeds supplied by feed millers, the quality of which determines the profit margin of the farmers. The presence of pathogenic microbes, however, tends to deplete the nutritive value of these poultry and fish diets. This study, therefore, focused on assessing the prevalence of micro-organisms in commercial poultry and fish feeds sold at Kisenyi Market, Uganda. Method: Poultry and fish feeds were randomly sampled and examined for their microbiological qualities using standard microbiological and analytical methods. The isolates were identified according to their cultural, microscopic, and biochemical properties. Results: A total of 42 micro-organisms were isolated, including; Citrobacter spp (4.76%), Corynebacterium spp (9.52%), E. coli (2.38%), and Enterococcus spp (35.71%) Proteus spp (2.38%) and S. aureus (45.2%). Comparing contamination in pelleted and non-pelleted feeds, there was no significant difference in the microbial contamination (feeds (X2 = 7.287, P> 0.05). Their susceptibility pattern revealed major resistance of; S. aureus to Gentamycin (78.95%), Corynebacterium spp to linezolid (100%), Enterococcus spp to Gentamycin (100%), and negative rod enterococcus to Cefoxitin (100%). Conclusion: The presence of a high level of pathogenic micro-organisms in the selected feeds offered to poultry and fish predisposes them to health hazards, with resultant economic loss. Therefore, the commercial feeds should be periodically examined for biosafety, to reduce or prevent the risk of cross-contamination of poultry and poultry products with resistant bacterial strains.